2007
DOI: 10.1136/jmg.2007.051276
|View full text |Cite
|
Sign up to set email alerts
|

SOS1 is the second most common Noonan gene but plays no major role in cardio-facio-cutaneous syndrome

Abstract: We have confirmed SOS1 as the second major gene for NS. Patients carrying mutations in this gene have a distinctive phenotype with frequent ectodermal anomalies such as keratosis pilaris and curly hair. However, the clinical picture associated with SOS1 mutations is different from that of CFCS. These findings corroborate that, despite being caused by gain-of-function mutations in molecules belonging to the same pathway, NS and CFCS scarcely overlap genotypically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
126
5
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(160 citation statements)
references
References 26 publications
19
126
5
10
Order By: Relevance
“…The mutation detection rate was lower than those reported in previous reports: 12/57 (21%) of cases with NS without PTPN11, KRAS and BRAF mutations (Roberts et al 2007), 22/129 (17%) patients with NS without PTPN11 and KRAS mutations (Tartaglia et al 2007), and 28% of patients with NS without mutations in PTPN11, KRAS, BRAF and MAP2K1/2 (Zenker et al 2007a). The lower detection rate in our study might be due to the smaller size of our cohorts.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The mutation detection rate was lower than those reported in previous reports: 12/57 (21%) of cases with NS without PTPN11, KRAS and BRAF mutations (Roberts et al 2007), 22/129 (17%) patients with NS without PTPN11 and KRAS mutations (Tartaglia et al 2007), and 28% of patients with NS without mutations in PTPN11, KRAS, BRAF and MAP2K1/2 (Zenker et al 2007a). The lower detection rate in our study might be due to the smaller size of our cohorts.…”
Section: Discussioncontrasting
confidence: 68%
“…A c.2999G [ A (S1000 N) mutation was identified in a patient with CFC syndrome. The substitution was identified in an unaffected mother and may represent SNP or a weak allele (Roberts et al 2007;Tartaglia et al 2007;Zenker et al 2007a). A P655L, which has been reported as a SNP or a weak allele (Roberts et al 2007;Tartaglia et al 2007;Zenker et al 2007a), was found in 3 out of 14 CFC patients from France.…”
Section: Mutation Analysis In Patientsmentioning
confidence: 97%
See 2 more Smart Citations
“…The analysis of SOS1 illustrates the individualized approach for each syndrome and mutation. Since Roberts et al [2007] listed each patient allowing complete analysis, and Zenker et al [2007b] provided a summary table useful for many data points, both references were used in a complementary fashion; a smaller series [Narumi et al, 2008] was omitted as per general methods. A condensed comparison is shown in Table VI based on study patient data only.…”
Section: Comparison With Rasopathiesmentioning
confidence: 99%